2012
DOI: 10.1002/cjce.21637
|View full text |Cite
|
Sign up to set email alerts
|

Transient kinetics of n‐butane partial oxidation at elevated pressure

Abstract: A transient Mars-van Krevelen type kinetic model was developed for n-butane partial oxidation over vanadyl pyrophosphate (VPP) catalyst. The model validity was verified over a relatively wide range of redox feed compositions as well as higher reactor pressure (410 kPa). Oxygen and n-butane conversion increased with higher pressure while maleic anhydride (MA) selectivity decreased by as much as 20%. However, the overall MA yield was enhanced by up to 30%. High pressure maintains the catalyst in a higher oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…[25] We advocate that words and text be concise (limit redundancy) and precise (rather than vague), that verbs be active (not passive) and vigorous (avoid delexical verbs and verb mutilation). Metadiscourse often adds unnecessary words like hedges, boosts, and signposts: [11] feeble verb, verb mutilation estimate were applied to analyze [12] [13] feeble verb characterize enable the characterization feeble verb, verb mutilation characterize experienced fragmentation feeble verb, verb mutilation fragment give good agreement [14] delexical, verb mutilation agree have an effect delexical, verb mutilation affect make an assessment delexical, verb mutilation assess observations have been made [15] verb mutilation, passive observe obtain a clear understanding delexical, verb mutilation, redundant understand accumulation of ions does not occur [16] verb mutilation, feeble verb ions do not accumulate perform an operation delexical, verb mutilation operate provide an explanation delexical, verb mutilation explain predictions show close agreement [17] feeble verb, verb mutilation, vague agree take into consideration delexical, verb mutilation consider by trying to minimize [18] hedging minimizing used for comparing feeble verb compare 5. 'Revise Sentences over 30 Words Long' [26] Identify metadiscourse in the following paragraph:…”
Section: -Hedging B)mentioning
confidence: 98%
See 1 more Smart Citation
“…[25] We advocate that words and text be concise (limit redundancy) and precise (rather than vague), that verbs be active (not passive) and vigorous (avoid delexical verbs and verb mutilation). Metadiscourse often adds unnecessary words like hedges, boosts, and signposts: [11] feeble verb, verb mutilation estimate were applied to analyze [12] [13] feeble verb characterize enable the characterization feeble verb, verb mutilation characterize experienced fragmentation feeble verb, verb mutilation fragment give good agreement [14] delexical, verb mutilation agree have an effect delexical, verb mutilation affect make an assessment delexical, verb mutilation assess observations have been made [15] verb mutilation, passive observe obtain a clear understanding delexical, verb mutilation, redundant understand accumulation of ions does not occur [16] verb mutilation, feeble verb ions do not accumulate perform an operation delexical, verb mutilation operate provide an explanation delexical, verb mutilation explain predictions show close agreement [17] feeble verb, verb mutilation, vague agree take into consideration delexical, verb mutilation consider by trying to minimize [18] hedging minimizing used for comparing feeble verb compare 5. 'Revise Sentences over 30 Words Long' [26] Identify metadiscourse in the following paragraph:…”
Section: -Hedging B)mentioning
confidence: 98%
“…The numbers in the graph represent the impact factor (N IF ) of the journal that published the article. 18. 'Publish and Flourish' [54] WoS categorizes arts and sciences into 250 disciplines.…”
Section: Papers and Postersmentioning
confidence: 99%
“…Shekari and Patience studied experimentally the effect of the oxidation period in cyclic CFB operation, and found that longer oxidation times were beneficial to MA yield. A further study by the same authors at elevated pressure showed that higher pressures improved the yield of MA, by maintaining the catalyst in a higher oxidation state and thus increasing catalytic activity, which more than compensated for the decrease in MA selectivity. Shekari and Patience proposed transient kinetics for n ‐butane oxidation for high pressure conditions.…”
Section: Introductionmentioning
confidence: 93%
“…The kinetics of this reaction has been the subject of many investigations [47][48][49][50][51][52][53][54][55][56][57][58]. A particular kinetic model for this reaction system is the widely cited work of Centi et al [48] in which the authors developed the model from the empirical data Table 2: General mass balance and mass transfer equations.…”
Section: Kinetic Modelmentioning
confidence: 98%